Computed tomography angiography-derived extracellular volume fraction predicts early recovery of left ventricular systolic function after transcatheter aortic valve replacement. (16th December 2020) - Han, Donghee; Tamarappoo, Balaji; Klein, Eyal; Tyler, Jeffrey; Chakravarty, Tarun; Otaki, Yuka; Miller, Robert; Eisenberg, Evann; Park, Rebekah; Singh, Siddharth; Shiota, Takahiro; Siegel, Robert; et al.
Abstract: Aims : Recovery of left ventricular ejection fraction (LVEF) after aortic valve replacement has prognostic importance in patients with aortic stenosis (AS). The mechanism by which myocardial fibrosis impacts LVEF recovery in AS is not well characterized. We sought to evaluate the predictive value of extracellular volume fraction (ECV) quantified by cardiac CT angiography (CTA) for LVEF recovery in patients with AS after transcatheter aortic valve replacement (TAVR). Methods and results : In 109 pre-TAVR patients with LVEF <50% at baseline echocardiography, CTA-derived ECV was calculated as the ratio of change in CT attenuation of the myocardium and the left ventricular (LV) blood pool before and after contrast administration. Early LVEF recovery was defined as an absolute increase of ≥10% in LVEF measured by post-TAVR follow-up echocardiography within 6 months of the procedure. Early LVEF recovery was observed in 39 (36%) patients. The absolute increase in LVEF was 17.6 ± 8.8% in the LVEF recovery group and 0.9 ± 5.9% in the no LVEF recovery group ( P  < 0.001). ECV was significantly lower in patients with LVEF recovery compared with those without LVEF recovery (29.4 ± 6.1% vs. 33.2 ± 7.7%, respectively, P  = 0.009). In multivariable analysis, mean pressure gradient across the aortic valve [odds ratio (OR): 1.07, 95% confidence interval (CI): 1.03–1.11, P : 0.001], LV end-diastolic volume (OR: 0.99, 95% CI: 0.98–0.99, P : 0.035), and ECV (OR: 0.92, 95% CI: 0.86–0.99, P : 0.018) were independent predictors of early LVEF recovery. Conclusion : Increased myocardial ECV on CTA is associated with impaired LVEF recovery post-TAVR in severe AS patients with impaired LV systolic function.